Analisis Dampak Penggunaan Portable Sealer Terhadap Jumlah Drop Out Component di Lini Produksi Surface Mounting Technology - Adi Nugroho; Abdul Muchid (TEKNIK, 2021)
The study aims to reduce the drop out of components that occur in the surface-mounting technology production line of PT. TEC Indonesia. This effort is carried out by designing a portable sealer product to glue the cover tape and carrier tape component products made in the line. In order to obtain the best value indicator for product design, this study uses a quantitative factorial design technique to determine value reduce drop out of components in the surface mounting technology (SMT) production of the parameter combination use of adhesive strength produced by the product. Information on study data obtained through the concept of experimental design (DOE) using temperature and treatment time parameters resulting from the product's design. Results of the tests have been carried out. Information on the adhesive strength reaches standard is rated at a temperature 1200 C for one two and three seconds, which can produce adhesion of 0.029 Kgf (the standard value is at 0.02-0.07 Kgf). In addition, the number of drop-out components produced after using the product has decreased significantly to zero, which previously reached an average of two to three components that were damaged or defective (test data).